PERAN TOKOH AGAMA DALAM MEMBENTUK PERILAKU KEAGAMAAN PADA MASYARAKAT YANG GEMAR TERHADAP ORGEN TUNGGAL DI KELURAHAN 15 ULU KECAMATAN JAKABARING PALEMBANG - Muhammad Kurniawan; Alfi Julizun Azwar; Aristophan Firdaus (Jurnal Studi Agama, 2021)
The purpose of this study is to explain how the contribution of religious figures in shaping religious behavior in people who are fond of single organism and what are the supporting factors and constraints of religious figures in shaping religious behavior in people who like single organism in Kelurahan 15 Ulu, Jakabaring District, Palembang. The data collection method uses the interview method, documentation observation, the analysis used is a qualitative descriptive approach. The research argues that the role of religious figures in Kelurahan 15 Ulu, Jakabaring Palembang Subdistrict has been good in its implementation, but ineffective in its approach to the community, because religious figures do not really provide counseling or warning advice to people who like single organizations in broadcasting religious knowledge. Sometimes only during the lecture at the wedding reception there is a little question of public discipline in the entertainment of the single organization itself. And it just so happens that most people in Kelurahan 15 Ulu, Jakabaring Subdistrict, Palembang, are less aware of the knowledge of Religion and religious behavior. So that awareness of the knowledge of Religion in Kelurahan 15 Ulu Sub-district of Jakabaring Palembang is lacking in terms of entertainment for the single organization itself.